2019
DOI: 10.1111/jai.13983
|View full text |Cite
|
Sign up to set email alerts
|

Length‐weight relationships of six tropical estuarine fish species from Pulicat lagoon, India

Abstract: Length-weight relationships (LWRs) of six finfish species under two families of the order Perciformes collected from Pulicat lagoon (India) are presented in this study.The fish specimens were collected weekly from the catches of shore seine net (with a mesh size of 50mm at the main webbing and 10 mm at the cod end) operated in the lagoon at an average depth of 2.5 m by the local fishermen during the period from July 2018 to April 2019. This study reports the LWRs for five gobiid and one siganid fish species wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Whereas, condition factor value was ranged from 1.41 to 1.56, with a mean 1.49±0.04. The high coefficient of determination values achieved in the calculation of LWR and LLRs in the present study reduced ambiguity (Nallathambi et al, 2020) and indicated a good quality of the prediction and small dispersion of the data (Correia et al, 2018) for linear regression in the observed fish specimens of Catla catla.…”
Section: Resultsmentioning
confidence: 51%
“…Whereas, condition factor value was ranged from 1.41 to 1.56, with a mean 1.49±0.04. The high coefficient of determination values achieved in the calculation of LWR and LLRs in the present study reduced ambiguity (Nallathambi et al, 2020) and indicated a good quality of the prediction and small dispersion of the data (Correia et al, 2018) for linear regression in the observed fish specimens of Catla catla.…”
Section: Resultsmentioning
confidence: 51%
“…The present study showed that 'b' values of 3.1215-3.1819 may be considered within the expected range of fishes (Froese, 2006;Sivadas, Sureshkumar, & Kannan, 2020) as different variables including sampling preference such as different fishing gears and mesh size, geographic area, seasons, feeding habits, population, gonad condition, parasitic infection, physiological factors and environmental parameter may affect the outcome of the study (Moutopoulos & Stergiou, 2002). The lower r 2 values in this study might be due to following limitation (a) measurements were made very restricted to narrow size range of these species, where the smaller size classes were missing (b) observation of similar body form during different seasons (Gupta, Sarkar, Bhardwaj, & Pal, 2011) (c) over-representation of the certain size range (Kodeeswaran et al, 2020) and (d) different geographic collection (Moulitharan et al, 2020). This study can be used to understand the basic biological parameters of these clupeid fishes.…”
Section: Discussionmentioning
confidence: 86%
“…The most appreciated species by fishermen are two catfishes that belong to the Ictaluridae family, Ictalurus balsanus (Jordan & Snyder, 1899) [11] a native of the basin, and I. punctatus (Rafinesque, 1818) [19] which was introduced as a fishing alternative (Mejía-Mojica et al, 2013) [14] . The introduction of exotic species to native ecosystems, in conjunction with the over-exploitation of fishery resources, are among the main threats to fish diversity, and directly impact ecosystem functioning ( [22,23,13,9,17,4] . This research analyzes the length-weight relationship for these two catfish species, which are subject to lowscale commercial fishing.…”
Section: Introductionmentioning
confidence: 99%